IGR J18249−3243: a new GeV-emitting FR II and the emerging population of high-energy radio galaxies. Issue 1 (31st March 2022) - Bruni, G; Bassani, L; Persic, M; Rephaeli, Y; Malizia, A; Molina, M; Fiocchi, M; Ricci, R; Wieringa, M H; Giroletti, M; Panessa, F; Bazzano, A; et al.
ABSTRACT: The advent of new all-sky radio surveys such as the VLA Sky Survey and the Rapid ASKAP Continuum Survey, performed with the latest generation radio telescopes, is opening new possibilities on the classification and study of extragalactic γ-ray sources, specially the underrepresented ones like radio galaxies. In particular, the enhanced sensitivity (sub-mJy level) and resolution (a few arcsec) provides a better morphological and spectral classification. In this work, we present the reclassification of a Fermi /Large Area Telescope (LAT) source as a new Fanaroff–Riley II radio galaxy from the International Gamma-Ray Astrophysics Laboratory sample found to emit at GeV energies. Through a broad-band spectral fitting from radio to γ-ray, we find that the commonly invoked jet contribution is not sufficient to account for the observed γ-ray flux. Our modelling suggests that the observed emission could mainly originate in the lobes (rather than in the radio core) by inverse Compton scattering of radio-emitting electrons off the ambient photon fields. In addition, we cross-correlated the latest generation radio surveys with a list of Fermi /LAT candidate misaligned AGN from the literature, finding four new radio galaxies with a double-lobed morphology. Additional four objects could be classified as such thanks to previous studies in the literature, for a total of nine new radio galaxies with GeV emission presented in this work. We foresee that further objects of this class might be found in the near future with the advent of the Square Kilometer Array, populating the GeV sky.